APPLICATION OF THE TIME TOKEN LEARNING MODEL TO IMPROVE STUDENT LEARNING ACTIVITIES ON THE THEME OF LEADERSHIP IN CLASS VI OF SD NEGERI 44 BANDA ACEH - Munira, Annisa; Fitri, Aida; Hasniyati, Hasniyati (Elementary Education Research, 2025)
This problem occurs because student learning activity is still low, when the learning process is taking place, students are seen busy chatting with their classmates, which results in the meaninglessness of learning where each student can only remember the lesson given, not understand it. The aim of this research is to describe the application of the Time Token learning model, teacher activities, and student learning activities on the Leadership Theme in Class VI of SD Negeri 44 Banda Aceh. The subjects of this research were 29 students. The data collection techniques used are observation and tests. And the data analysis used is descriptive qualitative using an average formula for teacher and student learning activities. The results of data analysis show an increase in student learning activity tests in cycle I with a percentage score of 57.3%, which is in the low category. In cycle II, the percentage score was 68.9%, including the sufficient category. Teacher activities in the learning process in cycle I with a percentage value of 82% are included in the good category. In cycle II, the percentage score was 93%, including the very good category. Student activity also showed an increase, namely in the first cycle they obtained a percentage score of 71.2% in the good category and in the second cycle they obtained a percentage score of 83.3% with very good criteria, so it was determined that this research was sufficient for only the second cycle. From various data analyzes carried out it can be concluded that the application of the Time Token Learning Model to Improve Student Learning Activities on the Leadership Theme in Class VI of SD Negeri 44 Banda Aceh has increased significantly